Clade Ib basic helix-loop-helix transcription factor, bHLH101, acts as a regulatory component in photo-oxidative stress responses. (September 2018) - Noshi, Masahiro; Tanabe, Noriaki; Okamoto, Yutaka; Mori, Daisuke; Ohme-Takagi, Masaru; Tamoi, Masahiro; Shigeoka, Shigeru
Highlights: Expression of clade Ib bHLH genes were decreased by oxidative stresses. Dominant negative expression of bHLH101 increased oxidative stress sensitivity. Overexpression of bHLH101 decreased oxidative stress sensitivity. tAPX silencing accelerated FCR activity induction under iron-deficient conditions. bHLH101 is a component in chloroplastic H2 O2 mediated biotic stress responses. Abstract: The accumulation of reactive oxygen species (ROS) leads to oxidative damage; however, ROS also acts as signaling molecules. We previously demonstrated that the inducible silencing of thylakoid membrane-bound ascorbate peroxidase Arabidopsis plants (IS-tAPX) accumulated H2 O2 in their chloroplasts, resulting in the clarification of ROS-responsive genes. In IS-tAPX plants, the transcript levels of the basic helix-loop-helix (bHLH) transcription factor bHLH101, which belongs to clade Ib bHLH, were down-regulated. In order to investigate the participation of bHLH101 in chloroplastic H2 O2 -mediated signaling, we isolated dominant negative expression mutants of bHLH101 ( DN-bHLH101 ). DN-bHLH101 plants showed a significant phenotype that was sensitive to a methylviologen treatment, even under iron-sufficient conditions. Furthermore, the knock out mutant of bHLH101 showed a photo-oxidative sensitive phenotype, indicating that other clade Ib bHLHs do not compensate for the function of bHLH101. Thus, bHLH101 appears to act as a regulatory component in photo-oxidative stress responses. We also found that ferric chelate reductase activity was stronger in IS-tAPX plants than in control plants, suggesting that there is a close relationship between iron metabolism and oxidative stress responses.